2006
DOI: 10.1063/1.2171480
|View full text |Cite
|
Sign up to set email alerts
|

Organic photocouplers consisting of organic light-emitting diodes and organic photoresistors

Abstract: We have fabricated one kind of organic photocoupler with organic light-emitting diode as the input unit and pentacene photoresistor as the output unit. The wavelength of the emitting light was 522nm. The output current of the photocoupler linearly increased with its input current and the ratio of the transfer current density reached 3. When the output voltages were 60V, the ratio of the maximum output current to the minimum output current was 150. The breakdown voltage between the input unit and the output uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Thus, the first organic optocouplers were carried out by Yu et al [6], the sensitivity of the device is about 10 À1 A/W and the current transfer ratio (CTR) of about 2 Â 10 À3 . Several other research works [7][8][9] have been reported on the optocoupler performance and their potential applications. Tang et al [8] have noticed that the optocoupler with organic phototransistors may present a current transfer ratio higher than the organic photodiodes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the first organic optocouplers were carried out by Yu et al [6], the sensitivity of the device is about 10 À1 A/W and the current transfer ratio (CTR) of about 2 Â 10 À3 . Several other research works [7][8][9] have been reported on the optocoupler performance and their potential applications. Tang et al [8] have noticed that the optocoupler with organic phototransistors may present a current transfer ratio higher than the organic photodiodes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, various authors [1][2][3][4][5][6] showed the relevance of illumination effects on the electrical performance of OTFTs for various applications: photodetectors, light activated memory devices, amplifiers or switches controlled by light excitation. In this latter case, the device can be integrated with an organic light emitting diode (OLED) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in microelectronic technologies. Compared with the inorganic photocoupler, the organic photocoupler has many advantages, such as light weight, low cost, flexibility et al Up to now, few research groups engage this job [6,12] . In this paper, an organic photocoupler device composed of an OLED and an OPV unit is constructed, with 520 nm OLED emissive light wavelength as the input light and the P3HT:PCBM bulk heterojunction active layer as the output detector respectively.…”
mentioning
confidence: 99%
“…In recent years many types of organic electronic and optoelectronic devices have got commercial availability, which made the organic electronics and devices become quite active. Since the efficiency of the organic light emitting diodes(OLEDs) was highly improved by C. W. Tang in 1987 [5] , the performance of OLEDs has made great progress in the past decade years [6][7][8] . Meanwhile, organic polymeric bulk heterojunction photovoltaic materials and devices (OPVs) have been developed so fast in recent years, and the highest efficiency of OPVs has reached 6.5% [9] .…”
mentioning
confidence: 99%